Political Rise or Standstill: Chinese-Indonesian Oligarchs in the 2014 National Legislative Election - Yuhao Wen (Indonesian Journal of International Relations, 2017)
Stereotype and suspicion toward certain ethnic minorities of the country has never left Indonesia’s story of social diversity. Growing participation and greater representation of Chinese-Indonesians in national and local election have demonstrated an inspiring progress of the country’s ongoing democratization which encourages the recognition of minority’s ethnic identity in wider society. Based on this context, this paper aims to introduce the general performance of Chinese-Indonesian candidates in the legislative election at the state level since 1999, with a focus on analysing media tycoon Hary Tanoesoedibjo’s (or Hary Tano) experience in the 2014 election, in which he has been credited by political scientists and Chinese-Indonesian scholars for a certain degree of break-through in the Indonesian political landscape. Such story of success, however, does not necessarily indicate any trend that Chinese-Indonesian politicians in general have obtained the same degree of equality in politics as their indigenous counterparts. The tactic that Hary Tano has adopted is to expand his political clout through buying-off minor parties. Yet, in practice the underlying social norms of the status quo means that there is a long road ahead until Chinese-Indonesian oligarchs are taken seriously as political actors rather than used for short-term political gain.